Mechanisms of radiative and nonradiative recombination in ZnSe:Cr and ZnSe:Fe: Примесные состояния в полупроводниках с переходными элементами - Godlewski, M.; Surma, M.; Ivanov, V.Yu.; Surkova, T.P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Possible applications of ZnSe:Cr in optoelectronics are discussed. It is shown that 2+ to 1+ photo-ionization of chromium results in efficient pumping of Cr2+ intrashell emission and in energy up-conversion from green to blue. A distinct difference in efficiency of the energy up-conversion is observed between chromium and iron doped ZnSe samples. This difference we relate to a very efficient Auger mechanism of photoluminescence quenching in Fe-doped samples. We further demonstrate an anticorrelation of intensity of mid-infrared Cr emission and up-converted blue emission of ZnSe.